Analisis Kemampuan Pemecahan Masalah Siswa dalam Menyelesaikan Soal Cerita Berdasarkan Tahapan Polya Materi Bangun Datar - Rani Dina Listari; Sukamto Sukamto; M. Yusuf Setia Wardana (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
This study aims to 1) analyze how the students problem-solving abilities in solving story problems based on the polya stages in the two-dimentional figure of class IV SD Negeri Gemblengmulyo Rembang, 2) to find out how to improve students' problem-solving abilities in solving story problems based on the stages of the pattern. This research uses descriptive qualitative research. Data collection in this study was carried out by means of written tests, interviews, and documentation. Taking the subject in this study using purposive sampling technique. Interviews were conducted with research subjects and class teachers. The result of this research is that low-ability students are quite able to go through the stages of understanding the problem and compiling a solution plan. Students with moderate abilities are able to go through the stages of understanding the problem, compiling a resolution plan, and carrying out the completion plan. Meanwhile, high-ability students are able to go through all stages of Polya's problem solving.